GAMBARAN KEJADIAN GASTRITIS DI RSUD RATU ZALECHA MARTAPURA - Azizah; Agianto; Agustina, Rismia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Gastritis is inflammation in the mucosal layer and sub-mucosa of the stomach. The most commoncause is a bacterial infection of helicobacter pylori, autoimmune disorders and long-term use ofanti-inflammatory drugs (NSAIDs). This study aimed to describe the factors that influence theincidence of gastritis in RSUD Ratu Zalecha Martapura. This was a descriptive study withconsecutive sampling method. Sample of 33 respondents in hospitals Queen Zalecha Martapurawas gained. The instrument used in this study was a questionnaire. Data were analyzed byunivariate. The results showed that of the total respondents, 66.7% have no good diet, 57.6% hada type of food that is not good, 63.6% frequently use anti-pain medications and antiinflammatory, 81.8% claimed to have the stress of work, 63.6% non-smokers, and 78.7% does notdrink alcohol.